Proceedings 2001 ICRA. IEEE International Conference on Robotics and Automation (Cat. No.01CH37164)
DOI: 10.1109/robot.2001.932733
|View full text |Cite
|
Sign up to set email alerts
|

Orienting parts by inside-out pulling

Abstract: A common task in automated manufacturing processes is that of orienting (or feeding) parts prior to assembly. In this paper, we propose a new type of feeder. We consider sensorless orientation of polygonal parts with elevated edges by pull actions with an overhead finger. We show that any asymmetric convex polygonal part can be oriented by a sequence of pull operations. We give an Ç´Ò ¿ µ algorithm to compute the shortest sequence of pull operations to orient a convex polygonal part with Ò vertices, if such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The stable equilibrium that occurs when pulling along a straight line was recognized, without proof, by Mason [10], Lynch and Mason [8], and Berretty et al [2]. For completeness, we provide a proof in Subsection IV-A.…”
Section: Related Workmentioning
confidence: 87%
See 3 more Smart Citations
“…The stable equilibrium that occurs when pulling along a straight line was recognized, without proof, by Mason [10], Lynch and Mason [8], and Berretty et al [2]. For completeness, we provide a proof in Subsection IV-A.…”
Section: Related Workmentioning
confidence: 87%
“…For completeness, we provide a proof in Subsection IV-A. To the best of our knowledge, Berretty et al is the only work, apart from ours, to explicitly take advantage of this stability [2]. However, the method of Berretty et al is limited to orienting asymmetrical convex polygons.…”
Section: Related Workmentioning
confidence: 96%
See 2 more Smart Citations
“…Ability to capture an object clearly contributes to the robustness and success of grasping tasks as we can guarantee a successful grasp of an object when it cannot escape from the surrounding fingers during the entire grasping execution. 1 A comprehensive review on grasping works can be found in [2].…”
Section: Introductionmentioning
confidence: 99%